Biochar and nitrogen fertilizer co-application changed SOC content and fraction composition in Huang-Huai-Hai plain, China. (March 2022) - Dong, Linlin; Yang, Xiao; Shi, Linlin; Shen, Yuan; Wang, Lingqing; Wang, Jidong; Li, Chuanzhe; Zhang, Haidong
Abstract: Biochar can significantly enhance soil organic carbon (SOC) and crop yield, and it is therefore the preferred material for soil improvement in medium-low yield fields. In this study, a field experiment was designed to explore the impacts of biochar application on SOC content and fraction composition. Results indicated that incorporation of biochar into soil increased the SOC content by 26.9%–65.3% in the surface layer (0–10 cm) and 30.3%–63.0% in the subsurface layer (10–20 cm) of soil, while water-soluble organic carbon (WSOC) of the two layers was increased by 2.2–40.0% and 2.3–39.8%, respectively. Microbial biomass carbon decreased under conventional nitrogen treatments and increased with biochar addition under increased nitrogen application. The C:N value increased with biochar application, while the water-soluble C:N value of soil applied with 30 t ha −1 biochar was lower than that of soil applied with 15 t ha −1 biochar, both in the two tested soil layers. Wheat yield is evidently correlated with SOC, with the correlation coefficients of 0.919 and 0.952 in the surface and subsurface soil layers ( P < 0.01), respectively. Particularly, increasing fulvic and humic acid-like compounds of WSOC promoted the bioavailability of nutrient elements, thereby increasing the crop yields. Therefore, biochar application is an effective means to fertilize middle-low yield soils through increasing SOC sequestration and nutrient reserves, or adjusting soil C:N value to a proper range, thereby reducing nutrient loss and increasing wheat yield. Graphical abstract: Image 1 Highlights: Biochar addition increased SOC and WSOC in medium-low-yield farmland. Biochar combination nitrogen fertilizer application changed Soil C:N and affected wheat yield. Biochar application increased fulvic and humic acid-like components as detected by EEM analysis. Biochar is a carbon-rich production and widely used in improving soil quality and carbon sequestration.